WOMEN’S ARGUMENT ACROSS SOCIAL STATUS IN TWITTER - Nazriani Lubis (JURNAL PENELITIAN PENDIDIKAN BAHASA DAN SASTRA, 2016)
Theoritically women have the tendency to avoid the argumentsin face to face communication. While, Twitter mode allows the users of twitter do not need to be ashamed and reluctant in expressing their argument with 140 characters. The objectives of the research were to identify the types of arguments used by female across social status and to find out the factor underlying these types occured in that way.. To achieve the objectives, this research was conducted by applying descriptive qualitative design. The subject of this research was the three different social status females. The pair interaction was appeared to conduct this research, namely; female to female interaction across social status. The data was collected from the tweets with three different topics (death penalty, law and education) which posted on twitter by all the subjects. The data was analyzed by applying Mile’s ajd Hubberman’s model. The finding showed that female to female interaction argued by all types of arguments; negation, disjunction, conjunction, conditional and biconditional, women were siginificantly less aware with their status in establishing and maintaning the interaction. In short, those were less considarate with their interlocutors.